Factors affecting employment choices related to the major of funeral services for Chinese vocational college students - Jia, Libin; Liu, Jianyin (Nurture, 2024)
Objective: The aim of this research is to examine the factors that influence Chinese vocational college students who want to work in funeral services and to offer suggestions and strategies for encouraging students to work in the funeral service field for a longer period of time. Design/Method/Approach: This paper selects students from Chinese funeral colleges and universities for a questionnaire survey. The data was evaluated using regression and correlation analyses in addition to interviews. The factors that influence funeral students’ decisions to work in the funeral field were examined. Results: The results of the data analysis showed that psychological and emotional needs, employment intention and family support ranked among the top three influencing factors for funeral students choosing employment in the funeral industry. Conclusion: The factors influencing funeral students to choose employment in the funeral industry subjectively are that the actual work does not match the work expectations. Objectively, it is an unadaptation to professional roles.